Noncommutative coverings of quantum tori - Schwieger, Kay; Wagner, Stefan (Mathematica Scandinavica, 2020)
We investigate a framework for coverings of noncommutative spaces. Furthermore, we study noncommutative coverings of irrational quantum tori and characterize all such coverings that are connected in a reasonable sense.